Sources of information used by patients prior to elective surgery: a scoping review. Issue 8 (5th August 2019) - Atlas, Alvin; Milanese, Steve; Grimmer, Karen; Barras, Sarah; Stephens, Jacqueline H
Abstract : Objective: To describe the range and nature of available research regarding sources of information that patients access to inform their decisions about elective surgery. Design: Scoping review. Data sources: Peer-reviewed studies published until February 2019 from the six scientific literature databases were searched and included in the study: Medline, PubMed, CINAHL, Academic Search Premier, EMBASE and SCOPUS. Web searches for grey literature were conducted in Google, South Australia Department of Health, Commonwealth Department of Health (Australia) and My Aged Care from the Department of Social Services (Australia). Eligibility criteria: Studies with a focus on elective surgery information sources oriented to patients were eligible for inclusion. Only studies written in English were sought and no publication date or study restrictions were applied. Data extraction and synthesis: Included literature was described by National Health and Medical Council hierarchy of evidence, and data were extracted on country and year of publication, type of literature, who provided it and any information on end users. Information sources were categorised by type and how information was presented. Results: A pool of 1039 articles was reduced to 26 after screening for duplicates and non-relevant studies. Face-to-face exchanges were the most likely source of information prior to elective surgery (59.3%), printed information (55.6%) followed by e-learning (51.9%) and multimedia (14.8%). The face-to-face category included information provided by the physician/general practitioners/specialists, and family and friends. Printed information included brochures and pamphlets, e-learning consisted of internet sites or videos and the use of multimedia included different mixed media format. Conclusion: There is considerable variability regarding the types of information patients use in their decision to undergo elective surgery. The most common source of health information (face-to-face interaction with medical personnel) raises the question that the information provided could be incomplete and/or biased, and dependent on what their health provider knew or chose to tell them.